2021
DOI: 10.18632/aging.202968
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in fecal short chain fatty acids (SCFAs) and branched short-chain fatty acids (BCFAs) in men with benign prostatic hyperplasia (BPH) and metabolic syndrome (MetS)

Abstract: Gut microbiome-derived short-chain fatty acids (SCFAs) emerge in the process of fermentation of polysaccharides that resist digestion (dietary fiber, resistant starch). SCFAs have a very high immunomodulatory potential and ensure local homeostasis of the intestinal epithelium, which helps maintain the intestinal barrier. We analyzed the association between stool SCFAs levels acetic acid (C 2:0), propionic acid (C 3:0), isobutyric acid (C 4:0i), butyric acid (C 4:0n), isovaleric acid (C 5:0i) valeric acid (C 5:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 98 publications
1
21
0
Order By: Relevance
“…In addition, we also found the presence of low levels of isobutyric, valeric, and isovaleric acids (Figure 6D−F). Isobutyric acid and isovaleric acid are the end products of the catabolism of branched-chain amino acids (valine, leucine, and isoleucine) 51 from proteins present in the samples by the gut microbiota. The total branched short-chain fatty acids (BCFAs, sum of isobutyric acid and isovaleric acid, Figure 6H) produced by the mulberry polysaccharide fermentation did not differ between the groups but were significantly higher than in the Con and FOS groups.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In addition, we also found the presence of low levels of isobutyric, valeric, and isovaleric acids (Figure 6D−F). Isobutyric acid and isovaleric acid are the end products of the catabolism of branched-chain amino acids (valine, leucine, and isoleucine) 51 from proteins present in the samples by the gut microbiota. The total branched short-chain fatty acids (BCFAs, sum of isobutyric acid and isovaleric acid, Figure 6H) produced by the mulberry polysaccharide fermentation did not differ between the groups but were significantly higher than in the Con and FOS groups.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Interestingly, patients with BPH have higher fecal isobutyric acid and isovaleric levels than healthy controls, and isobutyric acid, isovaleric acid, and isochronic acid were associated with the occurrence of metabolic syndrome in patients with BPH. 41 Furthermore, the Firmicutes/Bacteroidetes ratio was significantly higher in Japanese men with enlarged prostates than in men with normal-size prostates. 42 Similar mechanisms may be involved in the development of prostate cancer and BPH.…”
Section: Gut Microbiome and Prostate Cancermentioning
confidence: 92%
“…SCFAs, a major metabolite of the gut microbiota, regulate prostate cancer growth via systemic and local prostate IGF‐1. Interestingly, patients with BPH have higher fecal isobutyric acid and isovaleric levels than healthy controls, and isobutyric acid, isovaleric acid, and isochronic acid were associated with the occurrence of metabolic syndrome in patients with BPH 41 . Furthermore, the Firmicutes/Bacteroidetes ratio was significantly higher in Japanese men with enlarged prostates than in men with normal‐size prostates 42 .…”
Section: Gut Microbiome and Prostate Cancermentioning
confidence: 99%
“…This interestingly interplay between microbiome and gut can influence the development of MetS in patients with BPH due to the production of fatty acids. Authors also showed that the production of short chain fatty acids is accompanied by the production of harmful metabolites that contribute to the damage of the intestinal barrier and consequently to the penetration of bacterial and inflammatory factors into the blood with increasing of prostate gland inflammation and proliferation of prostate cells (7).…”
Section: Research Challengesmentioning
confidence: 99%